The Labor of Informational Democracy: A Library and Information Science Framework for Evaluating the Democratic Potential in Socially- Generated Information - Cope, Jonathan (Progressive community action: Critical theory and social justice in library and information science, 2016)
This essay outlines a framework that LIS can use to analyze socially-generated information. The proposed evaluative framework involves three democratic horizons of analysis: the level of access, the level of production, and the level of communicative speech. This inquiry synthesizes the political economy of communication/librarianship, autonomist Marxist insights about the dematerialization of labor in late capitalism, and the concerns of contemporary democratic theory. The essay concludes with a set of proposals for LIS to pursue research and policies that use a critical theoretical framework linking the realm of production (i.e., labor) with communicative democracy.
Keywords: MARX, Karl, 1818-1883; dematerialization of labor; informational democracy; late capitalism

Treble Troubles? Marketization, Social Protection and Emancipation Considered Through the Lens of Slavery - Davidson, Julia O’Connell (The Commonalities of Global Crises, 2016)
This chapter considers white European and American thinking on transatlantic slavery historically and, more briefly, in relation to today’s antislavery movement. Combining historical longue durée and a critical engagement with Nancy Fraser’s neo-Polanyian position, O’Connell Davidson shows that abolitionists were, and are, hard to fix as proponents of either market freedom or social protection, or indeed of ‘emancipation’. The postabolition experience of freed slaves shows that marketization, social protection and emancipation are not fully disarticulable political forces, suggesting that the idea of the ‘triple movement’ may be less useful for those committed to a politics of nondomination than it may initially appear.
Keywords: economics; public choice; slavery; social choice; social inequality; social protection; social structure; triple movement; welfare economics

Local Embeddedness - Pickles, John (International Encyclopedia of Geography: People, the Earth, Environment and Technology, 2016)
In economic geography and economic sociology, embeddedness refers to the ways in which relational, institutional, and cultural contexts shape economic life. In contrast to the undersocialized and utilitarian assumptions of neoclassical economics, rational choice theory, and new institutional economics, theories of embeddedness focus on the ways in which markets and society are variously articulated in particular societies, organizations, and places. Embeddedness in this sense is associated first and foremost with the work of Karl Polanyi. Polanyi argued that the market generally sought to disembed itself from social regulation, while society responded by attempting to socialize and regulate (re-embed) the excesses of unregulated markets. It is also associated with the work of Granovetter in economic sociology, who cautioned against oversocializing, as well as undersocializing, the economy, in favor of a much more detailed analysis of the specific ways in which social relations structured economic practices.
Keywords: POLANYI, Karl, 1886-1964; culture; economy; embeddedness; institutions; society; undersocialized

Singapore’s Social Contract Trilemma - Yeoh, Lam Keong; Auyong, Hawyee; Yeo, Andrew Zhi Jian (Globalization and Democracy in Southeast Asia, 2016)
The last 50 years of nation building has firmly established Singapore as a globally competitive and highly successful economy and city-state with one of the highest per capita incomes in the world. Singapore has achieved a prosperity undreamed of by its founders. How successfully Singapore can evolve into a fully developed nation, with a firm sense of national belonging, social cohesion, political legitimacy and participation—and not just a strong and successful developmental state—will depend on the extent to which the country is able to translate this success to broader social protection and democratic participation for her people, and the extent to which the country is able to forge a common national identity.
Keywords: FRASER, Nancy; Singapore; democracy; double movement; globalization; neo-Polanyian; policy studies; triple movement